Optimisation of corrosion control for lead in drinking water using computational modelling techniques - Hayes, Colin (Metals and related substances in drinking water series., 2013)
Optimisation of Corrosion Control for Lead in Drinking Water Using Computational Modelling Techniques is the first in the Research Report Series that is being published by the IWA Specialist Group on Metals and Related Substances in Drinking Water.